Results of calcein staining with three different concentrations and immersion times on the growth of Ostrea edulis - Verena Merk; Tanja Hausen; Timon Ameis; Bernadette Pogoda (PANGAEA, 2023)
Chemical dyes, such as Calcein, can be used to create incremental markings for measuring bivalve growth in shell cross-sections. For the European Oyster Ostrea edulis, potential negative effects and limits for this staining have not been assessed yet. In this study, Ostrea edulis individuals were stained with three different Calcein concentrations (100 mg l-1, 150 mg l-1, 200 mg l-1) at three different immersion times (6 h, 12 h, 24 h) to test the potential negative effects, the best incremental marking result and their potential to be used in growth measurements. The dataset includes the growth measurements of the individuals at the time of staining in Mai 2021 and the growth measurements after a growth period of 5 months (N=10 per treatment). In November 2021, the success of the staining was evaluated using a fluorescence microscope by measuring the increment from the staining line to the edge of the shell. For some individuals, a clean measurement was not possible. Either because the oysters were broken due to handling or because the line was not clearly visible. However, at least 7 or more oysters were measured per treatment. The survival rate for all concentrations and the control was 100%.